Hubungan Performa Fisik dengan Prognosis Pasien Gagal Jantung - Palilati, Nurfadhilah H.; Wantania, Frans E. N.; Rotty, Linda W. A. (e-CliniC, 2021)
Abstract: Heart failure is a serious health problem and a leading cause of death, illness, and poor quality of life. Although the diagnosis and treatment of this disease has significant progress, the prognosis is still poor. The physical performance of patients with heart failure, for example, measured by a 6-minute walking test can be used to assess the functional capacity and assess the prognosis of the patient. This study was aimed to determine the relationship between physical performance and prognosis of patients with heart failure. This was a literature review study using literatures obtained from three databases, namely Pubmed, Science Direct, and Google Scholar. The keywords used in searching the literatures were "physical performance OR 6 minutes walking test AND heart failure prognosis" and their variations and translations. After the selection, 10 literatures were reviewed. The results showed that any decreases in distance of the 6-minute walking test and in walking speed would increase the risk of rehospitalization and mortality as reported in nine literatures. In conclusion, there was a significant relationship between physical performance and prognosis of patients with heart failure.Keywords: physical performance, prognosis of heart failureÂ Abstrak: Gagal jantung merupakan masalah kesehatan yang serius dan penyebab utama kematian, kesakitan, serta kualitas hidup yang buruk. Meskipun diagnosis dan pengobatan penyakit ini telah mengalami banyak kemajuan namun prognosisnya masih buruk. Performa fisik pasien gagal jantung contohnya diukur dengan tes jalan 6 menit dapat digunakan untuk menilai kapasitas fungsional dan menilai prognosis dari pasien. Penelitian ini bertujuan untuk mengetahui hubungan performa fisik dengan prognosis pasien gagal jantung. Jenis penelitian ialah literature review menggunakanÂ  literatur yang diperoleh dari tiga database yaitu Pubmed, Science Direct. dan Google Scholar. Kata kunci yang digunakan dalam pencarian artikel yaitu â€œphysical performance OR 6 minutes walking test AND heart failure prognosisâ€ dan berbagai variasi serta terjemahan. Hasil seleksi, mendapatkan 10 literature yang dikaji. Hasil penelitian mendapatkan bahwa setiap penurunan jarak yang ditempuh dalam uji jalan 6 menit dan penurunan waktu kecepatan berjalan dapat meningkatkan risiko rehospitalisasi dan kematian yang dilaporkan pada 9 literatur. Simpulan penelitian ini ialah terdapat hubungan bermakna antara performa fisik dengan prognosis pada pasien gagal jantung.Kata kunci: performa fisik, prognosis gagal jantungÂ